Nonstructural proteins of herpes simplex virus. I. Purification of the induced DNA polymerase. - Powell, K L (1977)
Herpes simplex virus-induced DNA polymerase purified by published methods was found to be contaminated with many others proteins, including virus structural proteins. Thus, DEAE-cellulose and phosphocellulose chromatography were used in combination with affinity chromatography to purify DNA polymerase from herpes simplex virus type 1- and type 2-infected cells. The purified enzyme retained unique features of the herpesvirus-induced DNA polymerase, including a requirement for high salt concentrations for maximal activity, a sensitivity to low phosphonoacetate concentrations, and the capacity to be neutralized by rabbit antiserum to herpesvirus-infected cells. By polyacrylamide gel electrophoresis, the purified DNA polymerase was associated with a virus-induced polypeptide of about 150,000 molecular weight.